An analysis of the secondary school off-campus student-teaching program of the Philippine Normal College its implications for teacher education in Thailand - Thauyngam, Komol 1949- (1974)
The subjects of this study were 12 supervisors of student teaching, 44 cooperating teachers, and 77 student teachers during the second semester of the school year 1973-1974. The philosophy of student teaching is largely based on pragmatism, humanism, and idealism and that student teaching aims to provide students with a genuine taste of on the job experience and the opportunity to synthesize, test and apply the courses. Supervisors reported that their problems are related to (a) the inadequate background of the student teacher and (b) students' lack of communication skills.
Thesis (M.Ed.)--University of the Philippines
Keywords: Philippine Normal College; Student teaching -- Philippines; Student teaching -- Thailand